Removal of disperse red 9 from textile wastewater using acid activated carbon and polypyrrole nano composite – A comparative study - Supriya, S.; Palanisamy, P.N. (IJRDO-Journal of Applied Science, 2016)
The present study analyses the feasibility of removing Disperse red 9 (DR9)from industrial effluents using two different adsorbents namely Phosphoric acidimpregnated Activated Carbon (PAC) and Polypyrrole Polymer Composite (PPC) preparedfrom Casuarina wood. Batch mode adsorption studies were performed in order toinvestigate the adsorption capacities of these adsorbents by varying initial dyeconcentration, agitation time, temperature and pH. A comparative study on the adsorptivecapacities of PAC and PPC were carried out and it was inferred that PPC had betteradsorption capacity than PAC at an initial concentration of 50 mg/L at 300C, 350C & 400C.The calculated qe values agree very well with experimental values. The regressioncoefficient values above 0.98 confirm that adsorption follows second order kinetics. Theincrease in Langmuir adsorption capacity (Q0) from 7.48 to 9.41 mg/g for PAC and 8.65 to11.73 mg/g for PPC on increasing the temperature from 300to 400C accounts for theendothermic nature of the process.